2019
DOI: 10.1016/j.cobeha.2018.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Creativity: linchpin in the quest for a viable theory of cultural evolution

Abstract: This paper outlines the implications of neural-level accounts of insight, and models of the conceptual interactions that underlie creativity, for a theory of cultural evolution. Since elements of human culture exhibit cumulative, adaptive, open-ended change, it seems reasonable to view culture as an evolutionary process, one fueled by creativity. Associative memory models of creativity and mathematical models of how concepts combine and transform through interaction with a context, support a view of creativity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…A more 'ecological' view is that they function not as fixed representations or identifiers, but as bridges between mind and world that are sensitive to context, and actively participate in the generation of meaning (Gabora, Rosch, & Aerts, 2008). This view is central to the Honing Theory of creativity (HT) (Gabora, 2010(Gabora, , 2017(Gabora, , 2018(Gabora, , 2019a(Gabora, , 2019b, which grew out of a particular mathematical approach to concept interactions (Aerts, Sozzo, & Veloz, 2016;Aerts, Broekaert, Gabora, & Sozzo, 2016;Aerts, Gabora, & Sozzo, 2013;Aerts & Gabora, 2005a, 2005bBusemeyer & Bruza, 2012;Gabora & Aerts, 2002;Pothos, Busemeyer, Shiffrin, & Yearsley, 2017). HT posits that we know ideas only indirectly, by how they appear from particular perspectives or contexts, but each context unavoidably influences how the idea is experienced and understood.…”
Section: Honing Theory Of Creativitymentioning
confidence: 99%
“…A more 'ecological' view is that they function not as fixed representations or identifiers, but as bridges between mind and world that are sensitive to context, and actively participate in the generation of meaning (Gabora, Rosch, & Aerts, 2008). This view is central to the Honing Theory of creativity (HT) (Gabora, 2010(Gabora, , 2017(Gabora, , 2018(Gabora, , 2019a(Gabora, , 2019b, which grew out of a particular mathematical approach to concept interactions (Aerts, Sozzo, & Veloz, 2016;Aerts, Broekaert, Gabora, & Sozzo, 2016;Aerts, Gabora, & Sozzo, 2013;Aerts & Gabora, 2005a, 2005bBusemeyer & Bruza, 2012;Gabora & Aerts, 2002;Pothos, Busemeyer, Shiffrin, & Yearsley, 2017). HT posits that we know ideas only indirectly, by how they appear from particular perspectives or contexts, but each context unavoidably influences how the idea is experienced and understood.…”
Section: Honing Theory Of Creativitymentioning
confidence: 99%
“…It has been proposed that autocatalytic networks hold the key to understanding the origins of any evolutionary process, including the OOC (Gabora, 1998(Gabora, , 2000(Gabora, , 2013Gabora & Aerts, 2009;Gabora & Steel, 2017). 3 This kind of evolution has been referred to as Self-Other Reorganization (SOR) because it interleaves internal self-organization with external interactions with other self-organizing networks (Gabora, 2019). In application to the OOC, the products and reactants are not catalytic molecules but MRs 4 of experiences, ideas, and chunks of knowledge, as well as more complex mental structures such as schemas and scripts.…”
Section: Introductionmentioning
confidence: 99%
“…It may thereby play an important role in fostering group identity, cohesion and cooperation [66] (see also [49]). 6 It has been suggested that creative cognition occurs through a Darwinian process [68], but this theory has been sharply criticized [69][70][71][72], and its current primary proponent now advocates a non-Darwinian version of the theory [73]. 7 Note that vertical and horizontal transmission must be defined with respect to the relevant evolutionary process.…”
Section: Concluding Commentsmentioning
confidence: 99%